Fertilization with B, Cu and Zn associated with forest residue management in eucalyptus plantations - Masullo, Liamara Santos (2022)
Micronutrient nutrition in eucalypt plantations is little discussed in studies and the application of fertilizers that supply these nutrients is done in an empirical and preventive manner, generating many doubts about the effectiveness and importance of its application. In addition, forest residue management techniques can influence the supply of these nutrients on forest sites, leading to the need to apply larger doses to attend the demand of eucalypt stands. Thus, this study aimed (1) to evaluate the dynamics of B, Cu and Zn in a eucalypt stand trying to identify the nutrient most limiting to the productivity; (2) to determine the total stocks, as well as evaluate the pools, of Cu and Zn in the soil, identifying the relationship of residue management on these dynamics; (3) to identify relationships between nutrition with B, Cu and Zn and increase on tolerance to biotic stresses - in this study the susceptibility to eucalyptus rust; and (4) to understand what are the relationships between nutrition with B, Cu and Zn that determine this behavior related to plant health. Two studies were conducted. The first was installed at the Itatinga Forest Science Experimental Station under a Ferralsol. The treatments were composed of the contrast between the application (CF) or non- of B, Cu and Zn (-B, Cu and Zn) associated with the removal (ReR) or maintenance (ReM) of forest residues. The second study was conducted in a greenhouse at the Center for Nuclear Energy in Agriculture - CENA and the aim was to evaluate the effects of B, Cu and Zn omission on growth and production of metabolites by plants. The results showed that the application of B and Zn caused an increase in the levels of these nutrients in the soil, but no impact on the volumetric growth of the trees was found. The non-application of B caused a reduction in the foliar contents of B, which subsequently resulted in a 25% reduction of B cycled biochemically. The fractioning of Cu and Zn showed that the soil evaluated presents a large reserve of these nutrients, mainly in forms of low to moderate access by plants (> 60%). The probable ability of Eucalyptus spp. to access forms of moderate lability could explain the low responsiveness of E. spp. to Cu and Zn fertilization. The results found indicate that foliar Cu contents present a strong negative correlation with eucalyptus rust severity. Adequate nutrition with Cu results in a greater capacity for lignin production by plants. Furthermore, the omission of B, Cu and Zn would be related to the production of other important compounds for the phytosanitary defense, such as flavonoids (more 45-75% in adequately cultivated plants). The management of forest residues caused a reduction in soil fertility, with a negative correlation between organic matter and cationic ion (Mg, Ca and K).